Diseño e implementación de un laboratorio de circuitos electrónicos en la Universidad Técnica de Cotopaxi sede La Maná del cantón La Maná, provincia de Cotopaxi, año 2013 - Reyes Oyos, Freddy Gustavo (2014)
This thesis arose from the need of students, teachers and Cotopaxi Technical University La Maná to improve the laboratory of electronic circuits and develop practical guidelines for students to achieve practical learning. Nowadays, the university does not have a suitable laboratory for practice and demonstrate the theoretical knowledge acquired in the classroom. Faced with this problem this research topic originated because it was made with the firm intention of clearing all theoretical and thus improve the teaching and learning process. The laboratory was implemented after to apply the necessary surveys to students and teachers of the career, in order to know what their weaknesses were.